Penfluridol induces endoplasmic reticulum stress leading to autophagy in pancreatic cancer - Alok Ranjan; Nadezhda German; Constantinos Mikelis; Kalkunte Srivenugopal; Sanjay K Srivastava (Tumor Biology, 2017)
Pancreatic cancer is one of the most aggressive and difficult to treat cancers. Experimental and clinical evidence suggests that high basal state autophagy in pancreatic tumors could induce resistance to chemotherapy. Recently, we have demonstrated that penfluridol suppresses pancreatic tumor growth by autophagy-mediated apoptosis both in vitro and in vivo; however, the mechanism of autophagy induction by penfluridol was not clear. Several studies have established that endoplasmic reticulum stress could lead to autophagy and inhibit tumor progression. In this study, we demonstrated that penfluridol induced endoplasmic reticulum stress in BxPC-3, AsPC-1, and Panc-1 pancreatic cancer cell lines as indicated by upregulation of endoplasmic reticulum stress markers such as binding protein (BIP), C/EBP homologous protein (CHOP) and inositol requiring 1α (IRE1α) after treatment with penfluridol in a concentration-dependent manner. Inhibiting endoplasmic reticulum stress by pretreatment with pharmacological inhibitors such as sodium phenylbutyrate and mithramycin or by silencing CHOP using CHOP small interfering RNA, blocked penfluridol-induced autophagy. These results clearly indicate that penfluridol-induced endoplasmic reticulum stress lead to autophagy in our model. Western blot analysis of subcutaneously implanted AsPC-1 and BxPC-3 tumors as well as orthotopically implanted Panc-1 tumors demonstrated upregulation of BIP, CHOP, and IRE1α expression in the tumor lysates from penfluridol-treated mice as compared to tumors from control mice. Altogether, our study establishes that penfluridol-induced endoplasmic reticulum stress leads to autophagy resulting in reduced pancreatic tumor growth. Our study opens a new therapeutic target for advanced chemotherapies against pancreatic cancer.